Histórias de vida de pessoas em sofrimento psíquico sobre a inclusão no trabalho na perspectiva da economia solidária: ecologia de saberes revelando que Recriart é preciso - Mazaro, Lisabelle Manente (2021)
Mental health care transformed the Brazilian context after the outbreak of the Psychiatric Reform movement in the late 1970s, especially with the replacement of asylum, violent and exclusionary models, that is, a hegemonic hospital-centered model with a model of hospitality more humanized, inclusive community care and concerned with the rights of people in psychological distress. Work is one of the axes of Psychiatric Reform, in addition to being a social right guaranteed to all Brazilians by the Federal Constitution of 1988. What is observed is that access to work for this population has been predominantly given through the solidary economy, due to its more ethical, human, inclusive, and solidary rationality, which vehemently contradicts the capitalist system. The solidary economy, due to its ideology, basic principles, production, and socio-cultural organization, has revealed its emancipatory potential in the scope of mental health. Thus, the present study has as its general objectives: to understand how Recriart participants perceive the impacts of their experience in this workspace on their life trajectory; and reflect on this inclusion in the light of the theoretical framework of Knowledge Ecology, Sociology of Absences and Sociology of Emergencies by Boaventura de Sousa Santos. The specific objectives are: to describe the Recriart timeline from its origin to the present day; and to verify which changes occurred in the life trajectory of these people from the inclusion in the work, as well as to describe their impacts, identified by the collaborators themselves, dialoguing with the adopted theoretical framework. This is a research with a qualitative approach, which makes use of the oral history of life and makes use of the timeline as a systematization tool of the Recriart experience, in which 7 employees took part, namely: 1 professional from the incubation team accompanying the group, to trace the Recriart timeline and 6 working members of the same enterprise who narrated their life stories. The narratives were analyzed through categorical analysis, from the perspective of the sociologies of absences and emergencies and the ecology of knowledge, a theoretical-philosophical framework developed by the Portuguese sociologist Boaventura de Sousa Santos. The results indicate that Recriart is an economic solidarity enterprise in the field of mental health located in the city of São Carlos / SP, established in 2006, through a partnership between the Center for Psychosocial Care - CAPS II and the Multidisciplinary and Integrated Nucleus of Studies, Training, and Intervention in Solidarity Economy (NuMI-EcoSol) at the Federal University of São Carlos, whose main objective is the social inclusion of people through work. Over its 14 years, Recriart has undergone some changes and adaptations, conquered space and visibility in the municipality, becoming a reference for access to work for users of the São Carlos Mental Health Network. The narratives indicate that Recriart has a fundamental role in the lives of its workers, since, in addition to a workspace, it means appreciation as a human being, belonging to a group, exercising autonomy, expanding independence, (re) structuring of the routine, opportunity to make social exchanges, create bonds and develop affection. The results were subjected to categorical analysis and showed that employees are progressively transposing the logic of the patient - that subject who is assisted and accompanied by mental health care equipment - and recognizing his social place as a worker in spaces intended for work cooperative and supportive. There are clear differences between the place of assisted and the place of worker, which are decisive for the access to citizenship rights and social emancipation of the subjects, and the collaborators of this study are displacing work from the condition of treatment and placing it as a means of access to a different social place, of inclusion and citizenship. There is also the possibility of conquering autonomy through the work developed from the perspective of the Solidarity Economy and the results of this study point out that there is still a need for greater investment and incentive for autonomy to be achieved and exercised more effectively, not only in the work environment. work, but that it has repercussions on life in general. We concluded this work by demarcating the great potential for the emergence of work from the perspective of the Solidarity Economy, since, in addition to the economic issue, it establishes a space for social, cultural, and political exchanges, in addition to valuing the human being and all his knowledge.